Listening comprehension and working memory capacity in beginning L2 learners : an exploratory study - Fay de Azevedo, Aline (2012)
The objectives of present study were (1) to investigate whether individual differences in working memory capacity of L2 low-proficiency learners predict listening comprehension performance in a Cambridge proficiency exam (KET - Key English Test); and (2) to investigate whether learners improve their KET scores after two months of explicit training focusing on listening strategies. Participants included two groups of adult students (24 students in total) of English as a foreign language. The students were from an English Language Course in Porto Alegre. All students were Brazilian native speakers of Portuguese and were enrolled in classes that focus on the preparation for the Cambridge proficiency test. In the first part of the experiment the 24 adult students of English performed a working memory span test called BAMT-UFMG. In the second part of the experiment the experimental group (fourteen subjects in total), was administered two months (15 classes) of explicit training. The control group (ten subjects in total) was not given any training on listening strategies. The hypotheses of the study were: individual differences in working memory capacity would predict listening comprehension performance in the KET tasks; subjects would improve their scores in the KET tasks after 2 months of explicit training and awareness raising of listening strategies. The two hypotheses were confirmed. Individual differences in working memory capacity predicted listening comprehension performance in the KET tasks, r = .66 and p<0.001 for the working memory task , r = .38 and p< .031 for the Sentence comprehension task and r = .87 and p<.0001 for short term memory/speed of processing task. Subjects differed in their scores in the KET tasks after 2 months of explicit training and awareness raising of listening strategies, z = -1.96 (Wilcoxon Rank-Sum test for independent samples). The scores of the experimental group increased 14% after 2 months of explicit training on listening strategies, whereas the scores of the control group decreased 3%. Therefore, we believe that the present study contributed to research on the relationship between working memory capacity and listening comprehension in beginning L2 English learners. The study also corroborates the findings on individual differences in working memory capacity of Daneman and Carpenter (1980) and Just and Carpenter (1992), who state that the nature of a person's language comprehension depends on his or her working memory capacity.